Relationship aspects of muscle strength affecting the level of completion of the effectiveness of the long jump for the students of the first phase of the Faculty of Physical Education - University of Koya - Abdul Rahman, Hoshyar; Baez Tawfik, Rabaz; Abdel Yassin, Inas (Journal of Physical Education, 2012)
Find contains five sections: Part I: Definition of search: Building a solid base in the fitness depends on the muscle strength that are the basis of the development of other elements, particularly in the games competitive, as the power muscle is one of the manifestations of physical fitness, an important quality, and necessary for the individual in his daily life as well as the importance of active participation in events and sports, which requires all athletes give priority in their programs and approaches to achieve the goal they are trying to access it. Some researchers have dealt with special status, speed, and some other explosive power, and others Mtaulp power as an attribute physical task, and is one of the basic physical elements to the achievement of sporting achievement, On the subject of research study the aspects of muscle strength and their relationship to the level of Completion effective long jump. And as such play a major role in the development of a distinctive and muscles of the two men that are the main factor in the implementation of the Special Balothb movements and jumping events in athletics and field and especially in the implementation of the movement of the long jump. Research Objectives: The research aims to1.identify the aspects of muscle strength for the students of the first phase of the Faculty of Physical Education - University of Koya.2.identify the level of completion of the effectiveness of the long jump for the students of the first phase of the Faculty of Physical Education - University of Koya.3.identify the aspects of the relationship between muscle strength and level of achievement of the effectiveness of the long jump for the students of the first phase of the Sports College of Education University of Koya. Researcher assumes the following: That there are significant differences between aspects of muscle strength and level of achievement of the effectiveness of the broad jump for the students of the Faculty of Education University of Koya sport.The areas of research: ØThe human domain: (15) students in the first phase of the Faculty of Education University of Koya sport - for the academic year 2008-2009ØSpatial domain: Faculty of Education, Sport Stadium / University of KoyaØTemporal domain: for the period from 12/12/2009 and end 15/12/2009Part II: theoretical studies :Researcher dealt with in this section theoretical studies relevant to the study included the following main themes: muscle strength and importance, types of muscle strength, develop muscle strength modalities. And the phases of the technical effectiveness of the long jump.Part III: Research Methodology and procedures of the field: Use the researcher descriptive approach is adequate to the nature of the research and its objectives, the research sample was chosen in a deliberate, indiscriminate of the students of the Faculty of Physical Education - University of Koya - the first phase, also contains a section on tools and means of collecting data, and then was referred to the experience of reconnaissance and the main means of statistics.Part V:Included this section on the conclusions and recommendations reached by the researcher, and most important of these conclusions:1.There are significant differences between the strengths muscle Completion level of effectiveness of the long jump in the research sample.2.There are significant differences between the force characteristic secrecy of the muscles of the abdomen Completion level of effectiveness of the long jump in the research sample.3.There are important differences between the two aspects of the explosive power level of the effectiveness of the long jump Completion of the research sample.4.There were significant differences between the strengths of the back muscles to the maximum level of effectiveness of the long jump Completion of the research sample. The light of the findings obtained by the researcher recommended the following:1.to include the training process to study the arena and field exercises to strengthen abdominal muscles and legs and back.2.that are linked through exercises between training to strengthen the abdominal muscles and legs and back and training on the development of Completion jump.3.Conducting research and studies similar to other events in the athletics events and the field